2018
DOI: 10.1002/aelm.201700526
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Failure Mechanisms of Organic Photodetectors

Abstract: This work investigates in details the reliability of the PCDTBT:PC60BM-based

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Importantly, the classical boundary conditions introduced by Schottky 29 were used, which consists in keeping the electron and hole concentrations at electrode contacts constant under field and lighting and equal to their equilibrium values. Previous results have shown that these boundary conditions were in good agreement with experiments, accurately predicting the impact of contact work function modification and temperature 37 . Moreover, the HOMO and LUMO effective density of states N 0 was selected according to a common value found in literature 38 to 10 26 m -3 .…”
Section: ) Investigation Of the Main Features Of Gain In Organic Phosupporting
confidence: 67%
See 2 more Smart Citations
“…Importantly, the classical boundary conditions introduced by Schottky 29 were used, which consists in keeping the electron and hole concentrations at electrode contacts constant under field and lighting and equal to their equilibrium values. Previous results have shown that these boundary conditions were in good agreement with experiments, accurately predicting the impact of contact work function modification and temperature 37 . Moreover, the HOMO and LUMO effective density of states N 0 was selected according to a common value found in literature 38 to 10 26 m -3 .…”
Section: ) Investigation Of the Main Features Of Gain In Organic Phosupporting
confidence: 67%
“…In presence of light, photo generated electron may remain trapped within the traps, creating negative charges within the active layer of the device. The C n , C p trap parameters are not accurately known, and a large set of value can be found in the literature 37,42 . We decided arbitrary to use the value of 10 -13 cm 3 /s.…”
Section: ) Investigation Of the Main Features Of Gain In Organic Phomentioning
confidence: 99%
See 1 more Smart Citation
“…The open‐circuit voltage is however one of the key parameters of organic photovoltaic cells (OPVs), its origin and role in OPV performance have been extensively investigated . That being said, OPVs operate at high illumination intensities (≈100 mW cm −2 ) whereas OPDs tend to function under low irradiance to minimize overall power consumption and degradation mechanisms (such as photooxidation) . It is worth emphasizing that the V oc mode could actually lead to a self‐powered detector.…”
Section: Resultsmentioning
confidence: 99%
“…We illustrate this concept using a solution processed organic photodiode (OPD). OPDs are currently attracting extensive interest2,3,12–16 due primarily to their compatibility with large‐area, low‐cost production17 onto lightweight flexible substrates, which facilitates applications such as wearable sensors,18,19 smart packaging,20,21 and certain medical technologies 18,22–24. Such devices usually operate under an applied reverse bias,15 and have wavelength sensitivity that can extend from the UV to the near infra‐red (NIR) 25,26.…”
mentioning
confidence: 99%